CONCEPT AND REALISATION OF AUTOMATED ROOM CLIMATE CONTROL - Jelondz, D.; Spasokukotskiy, K.; Trankler, H.-R. (International Journal of Computing, 2002)
The paper deals with technical problems of automated decentralised indoor climate control in residential buildings. The lead value for the realisation of the control system is the objective thermal comfort. The measurement system to be designed works as a network between a large variety of different sensors and actuators. A comprehensive and flexible EIB networked instrumentation using cheap commercial and prototype sensors and actuators has been created and tested in a realistic test environment. In the paper, the conditions for a modern room climate control are discussed and the technical base for data acquisition system containing several different data collection channels is presented. Extensive measurements with the reliable, fully redundant data acquisition system showed its applicability in residential buildings. Based on the presented concept, different systems configurations can be realised. Following the results, a lowcost decentralised automated room climate control system is able to become a new standard in lowenergy buildings, opening a huge market potential.